1992
DOI: 10.1136/vr.131.5.100
|View full text |Cite
|
Sign up to set email alerts
|

Bog asphodel (Narthecium ossifragum) poisoning in cattle

Abstract: Fifteen cows among a herd of 50 suckler cows and calves rapidly lost body condition and became dull and anorexic after grazing pasture containing bog asphodel (Narthecium ossifragum) during the summer of 1989. The affected cows had evidence of kidney damage characterised by elevated plasma urea and creatinine concentrations. Eleven cows died and diffuse renal tubular necrosis was present in three cows which were examined post mortem. Similar renal lesions were reproduced experimentally by feeding bog asphodel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…A similar outbreak was reported in a cattle herd in Northern Ireland in 1989 (Malone et al, 1992). Experimental studies have confirmed nephrotoxic effect of bog asphodel in both cattle (Malone et al, 1992;Flå øyen et al, 1995b), sheep (Flå øyen et al, 1995a), and goats (Flåøyen et al, 1997). The kidney lesions described in these studies were similar to those found by us in moose.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…A similar outbreak was reported in a cattle herd in Northern Ireland in 1989 (Malone et al, 1992). Experimental studies have confirmed nephrotoxic effect of bog asphodel in both cattle (Malone et al, 1992;Flå øyen et al, 1995b), sheep (Flå øyen et al, 1995a), and goats (Flåøyen et al, 1997). The kidney lesions described in these studies were similar to those found by us in moose.…”
mentioning
confidence: 76%
“…Of these plants oak (Quercus spp. ), bog asphodel (Narthecium ossifragum), and field sorrel (Rumex acetosella) are reported to be nephrotoxic to domestic ruminants (Humphreys, 1988;Malone et al, 1992;Maxie, 1993;Flå øyen et al, 1995a, b, c). However, the nephrotoxicity of field sorrel is associated with oxalate precipitation in the renal tubules (Maxie, 1993), a finding that did not occur in our material.…”
mentioning
confidence: 99%
“…Four goats were kept as controls throughout the experiment (Nos. [22][23][24][25]. Two of these were anesthetized, and renal biopsies were taken on the same days as extract-treated animals (Nos.…”
Section: Animalsmentioning
confidence: 99%
“…The plant has also been associated with osteomalacia in cattle, therefore the species name ossifragum. 18 Several cases of severe bovine diseases related to ingestion of this plant were reported in Ireland in 1989, 22 and in 1992, similar such cases of disease were reported in cattle on pastures in Norway. 9,10 Clinical signs were depression, anorexia, melaena or fresh blood in the feces, and often diarrhea, leading to death in many cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation